Methodical approach to bankruptcy prediction model development (Revista de Investigaciones Universidad del Quindío, 2022)
There stands a possibility of crises in organizations, which are defined by objective elements, including unforeseen fluctuations in market circumstances, periodic technological modernizations, alterations in the production’s organization, staff change or external circumstances, and oftentimes political conditions. Bankruptcy is regarded as a crucial factor of crisis notion at enterprises. In fact, bankruptcy is a substantial factor in the structure of the market system, and its primary aim is to preserve social-economic procedures from the outcomes of inefficient actions of their participants and the failure to meet their tasks. As a result, this article mainly intends to analyze the methodical means and techniques for bankruptcy prediction model development. To that aim, several methods, including synthesis, assessment, analysis, comparison, generalization method, and system analysis are utilized. Based on the results, it can be concluded that the international authors incorporate the indicators calculated utilizing the information on financial outcomes as the most crucial indicators. In contrast,  Russian scholars and analysts are more concerned with the application of the enterprise property state.
Keywords: bankruptcy analysis; market system; bankruptcy prediction; bankruptcy analysis methods; political conditions